2015
DOI: 10.1371/journal.pgen.1005333
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous DNA and RNA Mapping of Somatic Mitochondrial Mutations across Diverse Human Cancers

Abstract: Somatic mutations in the nuclear genome are required for tumor formation, but the functional consequences of somatic mitochondrial DNA (mtDNA) mutations are less understood. Here we identify somatic mtDNA mutations across 527 tumors and 14 cancer types, using an approach that takes advantage of evidence from both genomic and transcriptomic sequencing. We find that there is selective pressure against deleterious coding mutations, supporting that functional mitochondria are required in tumor cells, and also obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
103
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 47 publications
(74 reference statements)
14
103
1
1
Order By: Relevance
“…Two recent large-scale efforts to examine the mutational landscape of the mitochondrial genome in over 2000 human cancers across more than 30 tumor types compared with normal tissue from the same patient by massively parallel DNA sequencing has revealed important insights (Ju et al, 2014; Stewart et al, 2015). These studies identified many somatic substitutions with strong replicative strand bias, with C to T and A to G transversions on the mitochondrial heavy strand indicative of mitochondrial polymerase G errors as the major cause of mutations.…”
Section: The Mitochondrial Genome In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent large-scale efforts to examine the mutational landscape of the mitochondrial genome in over 2000 human cancers across more than 30 tumor types compared with normal tissue from the same patient by massively parallel DNA sequencing has revealed important insights (Ju et al, 2014; Stewart et al, 2015). These studies identified many somatic substitutions with strong replicative strand bias, with C to T and A to G transversions on the mitochondrial heavy strand indicative of mitochondrial polymerase G errors as the major cause of mutations.…”
Section: The Mitochondrial Genome In Cancermentioning
confidence: 99%
“…This is surprising, given the close association of mitochondrial ROS production with mutations, which is apparently dwarfed by the frequency of polymerase errors that occur during the normal process of genome replication. More importantly, missense mutations are selectively neutral and drift toward homoplasmy, whereas there is negative selection for deleterious, pathogenic mutations that remain heteroplamic (Ju et al, 2014; Stewart et al, 2015). These findings clearly indicate that there is generally selective pressure in human cancers for retention of mitochondrial genome function.…”
Section: The Mitochondrial Genome In Cancermentioning
confidence: 99%
“…In contrast, DNA synthesis initiated at O L uses ssDNA as a template and, therefore, TWINKLE is not required. These strand-specific differences may influence the relative rate of H-and L-strand synthesis and could explain why there are strand-specific mtDNA mutation patterns, for example, as observed in cancer cells (115,116). In addition to the SDM, two alternative models for mtDNA replication have been suggested, that is, the model of ribonucleotide incorporation throughout the lagging strand (RITOLS) and the model of strand-coupled mtDNA replication (117)(118)(119)(120)(121).…”
Section: Figurementioning
confidence: 99%
“…The mitochondrial nucleoids are shown in blue, and the green structures represent cristae. 115 nm × 80 nm × 80 nm. Thus, the data predict that a single copy of mtDNA is fully coated and compacted by TFAM to form an irregularly shaped, slightly elongated nucleoid (Figure 7).…”
Section: Packaging Mtdna Into Mitochondrial Nucleoidsmentioning
confidence: 99%
“…At the genetic level, comparisons using full genome sequencing in patient-derived pairs of cancer and normal tissues across multiple tumor types revealed the existence of somatic mtDNA mutations in a majority of tumors [46,47] , with 31.1% of the tumors harboring multiple mtDNA mutations [47] . Unlike the nuclear genome, which contains two alleles of each gene, the mtDNA complement of a cell consists of hundreds to thousands of circular mtDNA molecules, allowing for different layers of mtDNA heterogeneity: alterations in mtDNA copy number, mutations in the mtDNA that occur in some but not all copies of the mtDNA genome within a cell (heteroplasmy), or mutations in the mtDNA that show dominance and accumulate until the mutant mtDNA becomes the only version present in the cell (homeoplasmy).…”
Section: Mitochondria Heterogeneity In Cancermentioning
confidence: 99%